Nursing of integrated Traditional Chinese and western medicine for a patient with ankylosing spondylitis complicated with ecthyma (1例强直性脊柱炎并发臁疮患者的中西医结合护理体会) - WANG Xiaodi (王晓娣); ZHI Hui (智慧); LIU Jinjing (刘津京); GUO Jing (郭晶) (Association of Integrative Nursing, 2022)
This paper summarized the nursing of integrated Traditional Chinese and western medicine for a patient with ankylosing spondylitis(AS) complicated with ecthyma. Based on the Traditional Chinese Medicine syndrome differentiation, TCM-characterized nursing technology such as Chinese Medicine collapse stains, moxibustion, acupoint massage, auricular acupoint sticking and pressing, dietary guidance were used jointly. Implementation of integrative nursing is potentially effective to relieve the pain and improve the ulcer healing. (本文总结1例强直性脊柱炎并发臁疮患者的中西医结合护理措施。在常规护理的基础上辨证施护, 合理应用中药塌渍、艾灸、穴位按摩、耳穴贴压、膳食指导等中医特色护理技术, 能有效缓解患者疼痛, 促进溃疡的早期愈合。)